CНИЖЕНИЕ ПОТЕРЬ АКТИВНОЙ МОЩНОСТИ В СЕТЯХ НИЗКОГО НАПРЯЖЕНИЯ С ВЫПРЯМИТЕЛЬНОЙ НАГРУЗКОЙ - Жаркин, А.Ф.; Новский, В.А.; Каплычный, Н.Н.; Козлов, А.В.; Малахатка, Д.А. (Інститут електродинаміки НАН України, Київ, 2017)
One of the methods of active power losses reducing in the low voltage network by connecting rectifier load to artificial zero point, which is created using a power zero sequence filters is considered. The special design of filters provides not only a essential reduction in active power losses in the low voltage distribution network, but also a significant improvement of power quality for consumers. References 8. figures 7.